Ghost rider wolverine ebook Weapons of vengeance. - Percy, Benjamin (Marvel Worldwide, Inc., 2024)
Collects Ghost Rider/Wolverine: Weapons of Vengeance Alpha (2023) #1, Ghost Rider (2022) #17, Wolverine (2020) #36, Ghost Rider/Wolverine: Weapons of Vengeance Omega (2023) #1. Are you ready for…the Hellverine?! Wolverine is the best there is at what he does - and what he does famously isn't very nice. When innocent blood is spilled, Johnny Blaze becomes the Ghost Rider, equipped to deal out punishment with the power of hellfire! And when a demonic serial killer murders innocent mutants, this deadly new villain brings these two forces of nature together! But what buried secret does this mysterious enemy share with Wolverine and Ghost Rider's never-before-seen first meeting in the past? Get ready for claws, chains and violence as only Benjamin Percy (WOLVERINE, GHOST RIDER) and Geoff Shaw (THANOS, GUARDIANS OF THE GALAXY) can deliver!